Impacto do uso de dados abertos sobre a assimetria de influência do lobby no Congresso Nacional - Felipe Lélis Moreira (2021)
The dissertation aimed to investigate the following problem: to what extent does the use of open data affect the asymmetry of influence of the lobbyists on the Brazilian National Congress? We started from the premise that there is an asymmetry of influence among lobbying actors (interest groups or individuals) and as hypotheses we speculated two types of results. The first would be in the sense that the use of open data does not matter, i.e., it does not interfere in the asymmetry of influence of the lobbyists on the National Congress. The second result rejects the previous hypothesis, assuming one of the following alternative hypotheses, that the asymmetry increased or, on the contrary, decreased in the case of the use of open data by the lobbyists. Before testing the hypotheses, a theoretical discussion was made about the conceptual frontiers of lobbying and the machine readability of public institutions, where the availability of open data is seen as a prerequisite of transparency in the 21st century. To test the research hypotheses, empirical evidence was collected in two stages. In the first stage, we collected quantitative data applying a survey directed at government relations professionals, and advocacy professionals. In the second stage, we collected qualitative data from semi-structured interviews that were conducted with open data intermediaries of the National Congress that offer technological solutions to support lobbying activities. It was concluded that there is evidence that the use of open data matters for lobbying purposes and that it can truly affect the asymmetry of influence on the Brazilian National Congress. However, regarding the direction of the impact of the use of open data on the asymmetry of influence, there is evidence that the asymmetry is both increased and decreased, due to issues related to the capacity of appropriation of open data and the respective technological tools that use them as an input to subsidize the lobbying activity of various social actors.